Renal Involvement of Sarcoidosis: Case Series and Review of the Literature - D, Lygerou; M, Bolaki; K, Stylianou; G, Margaritopoulos; EK, Dermitzaki; E, Vasarmidi; E, Drosataki; SA, Maragkou; A, Paraskevopoulos; G, Perisinaki; H, Gakiopoulou; I, Lambiri; et al. (Archives of Clinical and Medical Case Reports, 2019)
Sarcoidosis is a disease characterized by granulomatous inflammation potentially affecting multiple organ systems. Although it can affect any organ, lungs, lymph nodes, skin and eyes are most commonly involved. Renal sarcoidosis, although rare, remains a challenging clinical issue requiring mandatory treatment, given the risk of developing renal failure. Taking into consideration the rarity of the disease, data regarding its diagnosis and treatment are scarce. This case series describes seven cases of sarcoidosis with predominantly renal manifestations, and moreover provides a review of the current literature on renal sarcoidosis.